STUDY OF THE INHIBITORY EFFECTS OF VITAMIN E DERIVATIVES ON MITOCHONDRIAL COMPLEX II SUBUNIT USING MOLECULAR DOCKING - KARTIKA, IRMA RATNA; ERNAWATI, TENI; JUSMAN, Sri WIDIA A.; SADIKIN, MOHAMAD (International Journal of Applied Pharmaceutics, 2024)
Objective: The goal of this study was to create vitamin E derivatives and explore their potential anticancer properties using a computational approach. Methods: The Steglich method was used for the synthesis of the vitamin E-fatty acid (pentanoic acid, heptanoic acid, and octanoic acid) derivatives, with N,N'-dicyclohexylcarbodiimide (DCC) and 4-dimethylaminopyridine (DMAP) as the catalysts. The structure of the synthesized products was determined by ultraviolet-visible (UV-Vis) spectroscopy, fourier transform infrared (FTIR) spectroscopy, and liquid chromatography-mass spectrometry (LC-MS). Molecular docking was carried out on the succinate dehydrogenase (SDH) enzyme using AutoDockTools. Results: α–Tocopherol pentanoate (α–TP), α–tocopherol heptanoate (α–TH), and α–tocopherol octanoate (α–TO) were the three vitamin E derivatives synthesized in this study. Based on the results of molecular docking, the novel compounds (α–TP, α–TH, and α–TO) generated bond energies of-10.57,-9.61, and-9.20 kcal/mol, respectively. Conclusion: All newly synthesized compounds exhibited lower binding affinity values than α–tocopherol (α–T). This confirms that these compounds might not provide greater advantages than α-tocopherol in terms of inhibitory effects on mitochondrial complex II (CII).